1980
DOI: 10.1038/285480a0
|View full text |Cite
|
Sign up to set email alerts
|

Prostacyclin production by cultured smooth muscle cells from atherosclerotic rabbit aorta

Abstract: Prostacyclin (PGI2) synthesis seems to be one of the major physiological mechanisms involved in regulating platelet and vessel wall interactions. PGI2 is produced in large amounts by vascular endothelial cells, and vascular smooth muscle cells (SMC) also produce significant quantities. The capacity of SMC to produce PGI2, especially after endothelial injury, seems to be of importance. It is probably this type of situaton that is involved in the atherosclerotic process: experimental atherosclerosis in rabbits h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
18
1

Year Published

1981
1981
1989
1989

Publication Types

Select...
7
3

Relationship

0
10

Authors

Journals

citations
Cited by 90 publications
(20 citation statements)
references
References 10 publications
1
18
1
Order By: Relevance
“…Secondly, indomethacin and other cyclo-oxygenase inhibitors enhance adrenergically evoked contractions of rabbit mesenteric arteries (Malik et al, 1976;Armstrong & Thirsk, 1979;Hadhazy et al, 1984). Thirdly, vascular smooth muscle cells synthesize substantial amounts of prostacyclin (Baenzinger et al, 1979;Larrue et al, 1980). This also explains the lack of effect of endothelium removal on the potentiation produced by indomethacin in the present study.…”
Section: Discussionsupporting
confidence: 64%
“…Secondly, indomethacin and other cyclo-oxygenase inhibitors enhance adrenergically evoked contractions of rabbit mesenteric arteries (Malik et al, 1976;Armstrong & Thirsk, 1979;Hadhazy et al, 1984). Thirdly, vascular smooth muscle cells synthesize substantial amounts of prostacyclin (Baenzinger et al, 1979;Larrue et al, 1980). This also explains the lack of effect of endothelium removal on the potentiation produced by indomethacin in the present study.…”
Section: Discussionsupporting
confidence: 64%
“…D'Angelo, Villa, Mysliwiec, Donati & de Gaetano (1978) reported that human atheromatous plaques from three patients were incapable of prostacyclin production. Prostacyclin generation by atherosclerotic arterial tissue has been shown to be significantly lower than from normal arterial tissue but no difference was found between early and advanced atherosclerotic lesions (Sinzinger, Feigl & Silberbauer, 1979 (Larrue, Rigaud, Daret, Demond, Durand & Bricaud, 1980). In addition, it has been shown in rats that a vitamin E deficient diet leads to an increase in peroxide levels in the aortae and to a decrease in prostacyclin production in vitro (Okuma, Takayama & Uchino, 1980).…”
Section: Prostacyclin and Atherosclerosismentioning
confidence: 99%
“…9 - 23 Conversely, PGI 2 formation can be suppressed or abolished by indomethacin, aspirin, tranylcypromine, 15-hydroperoxyarachidonic acid, linoleic acid, low density lipoprotein, glucocorticoids, calcium channel blockers, and cigarette smoke condensate. 59 - 24 - 31 Physiologic alterations, such as disordered blood flow, mechanical stress, high blood pressure, stasis, and low oxygen tension, or morphologic changes can result in enhanced vascular PGI 2 production. 12 -2832 - 38 Mechanical trauma and endothelial injury due to excision, ex vivo storage, and surgical preparation of vein segments before grafting may acutely impair the capacity of the venous endothelium to generate PG^, 3 9 4 0 4 1 while the chronic response to venoarterial grafting is increased production.…”
mentioning
confidence: 99%